Carboxylated ferroferric oxide magnetic nano-microspheres and preparation method thereof

By preparing triferromagnetic nano microspheres of tetraoxide under alkaline conditions and carboxylation treatment was performed on their surfaces, the existing magnetic nano microspheres are easily oxidized, corroded and low adsorption capabilities, and the effect of improving their stability and adsorption performance is achieved.

CN119549124APending Publication Date: 2025-03-04XIAN NATU INTELLIGENT TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411858031.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing trioxide ferromagnetic nanomicrospheres are prone to oxidation in the air, are prone to corrosion and agglomeration in an acidic environment, and have a low ability to adsorb heavy metal pollutants.

Method used

Triferromagnetic nano microspheres of trioxide were prepared by co-precipitation using FeCl2·4H2O, FeCl3·6H2O, sodium citrate, PEG-4000 and anhydrous sodium metasilicate under alkaline conditions, and carboxylation treatment was introduced on their surface to improve their stability and adsorption properties.

Benefits of technology

The saturated magnetic field strength, stability, dispersion, acid resistance and heavy metal adsorption amount of trioxide ferromagnetic nano microspheres are improved, and the adsorption effect of the treatment of Cu2+, Al3+, Zn2+ and Ni2+ pollution is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005192421510000122
    Figure BDA0005192421510000122
Patent Text Reader

Abstract

The invention discloses carboxylated ferroferric oxide magnetic nano microspheres and a preparation method thereof, and belongs to the technical field of magnetic nano microsphere preparation.The preparation method comprises the following steps that cellulose and ferroferric oxide magnetic nano microspheres are prepared into composite magnetic nano microspheres through a gel method; the preparation method comprises the following steps: preparing ferroferric oxide magnetic nano-microspheres with strong magnetism and high stability, coating the surfaces of the ferroferric oxide magnetic nano-microspheres with a layer of cellulose gel layer containing hydroxyl groups, and carrying out combined action on hydroxyl and carboxyl introduced by amide reaction to obtain the carboxylated ferroferric oxide magnetic nano-microspheres. The dispersity and the stability of the carboxylated ferroferric oxide magnetic nano-microspheres during sewage treatment are improved, and the removal rate of heavy metals in sewage is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic nano-microsphere preparation, and in particular to carboxylated ferroferric oxide magnetic nano-microsphere and a preparation method thereof. Background Art

[0002] With the rapid advancement of industrialization, a large number of heavy metal ions are discharged into water bodies with industrial wastewater from mining and smelting, fertilizer manufacturing, battery manufacturing, papermaking, printing and dyeing textiles, etc., causing serious pollution. Biological treatment, membrane separation, chemical precipitation, ion exchange and photocatalysis are commonly used in the treatment of industrial wastewater, but these methods have their own limitations. For example, biological treatment has strict environmental requirements, membrane separation has high operating costs, chemical precipitation will produce a large amount of chemical sludge, and photocatalytic treatment rate is slow. The adsorption method is widely used in the adsorption of Cu in heavy metal wastewater due to its advantages such as wide source of materials, simple preparation process and low cost. 2+ 、Al 3+ 、Zn 2+ and Ni 2+ .

[0003] At present, Fe3O4 is the most widely used magnetic material in heavy metal wastewater treatment. It has become an ideal new adsorption material because of its large specific surface area, superparamagnetism, low cost and easy surface modification. However, Fe3O4 material is easily oxidized in the air, easy to corrode and agglomerate in acidic environment, and when treating heavy metal pollution in water bodies, Fe3O4 adsorbent exhibits low adsorption capacity due to limited diffusion or lack of sufficient active surface sites, which affects its application in treating Cu 2+ 、Al 3+ 、Zn 2+ and Ni 2+ Adsorption effect in case of contamination.

[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a carboxylated ferroferric oxide magnetic nano-microsphere and a preparation method thereof, so as to solve the technical problem that the saturation magnetic field intensity, stability, dispersibility, acid resistance and heavy metal adsorption capacity of ferroferric oxide magnetic nano-microspheres in the prior art need to be further improved.

[0006] The purpose of the present invention can be achieved by the following technical scheme: A method for preparing carboxylated ferroferric oxide magnetic nanoparticles, comprising the following steps:

[0007] S1. Place ethylenediaminetriaminepentaacetic acid and ammonia water in a three-necked flask at a temperature of 30-60°C, add acetic acid to adjust the pH to 6-7, add a catalyst, and keep the temperature for reaction for 1-2 hours to obtain a weak acid mixture;

[0008] S2. Place the composite magnetic nano-microspheres and the weak acid mixture in a three-necked flask at a temperature of 60-80° C., stir for 12-15 hours, and perform post-treatment to obtain carboxylated ferroferric oxide magnetic nano-microspheres.

[0009] The reaction principle for preparing carboxylated ferroferric oxide magnetic nanospheres is as follows:

[0010] Acetic acid is used to adjust the pH to 6-7, so that N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide generate active amide intermediates, further promoting the generation of amide bonds between amino groups on the surface of the composite magnetic nano-microspheres and part of the carboxyl groups of ethylenediaminetriaminepentaacetic acid, introducing carboxyl groups on the surface of the composite magnetic nano-microspheres, and N-hydroxysuccinimide can activate the carboxyl groups of ethylenediaminetriaminepentaacetic acid to form amide intermediates, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide stabilizes the intermediates to prevent hydrolysis, thereby improving the efficiency of the amide reaction and ensuring the stability of the cross-linking reaction.

[0011] Furthermore, the carboxylated ferroferric oxide magnetic nanospheres include: in step S1, the concentration of the ammonia water is 0.1-0.2 mol / L, the concentration of the acetic acid is 1.6-2.0 mol / L, the catalyst is composed of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a weight ratio of 1:1, and the dosage ratio of ethylenediaminetriaminepentaacetic acid, ammonia water and catalyst is 2-5 g:60-80 mL:0.5-1 g; in step S2, the dosage ratio of the composite magnetic nanospheres and the weak acid mixed solution is 2.5-5 g:50-80 mL, and the post-treatment includes: filtering the reaction solution, washing the precipitate with 0.2 mol / L Na2H2PO4 solution and deionized water for 1-2 times, drying, and grinding to obtain the carboxylated ferroferric oxide magnetic nanospheres.

[0012] Furthermore, the preparation method of the composite magnetic nanospheres comprises the following steps:

[0013] A1. Place urea, deionized water, NaOH and cellulose in a three-necked flask at a temperature of -15-15°C, adjust the speed to 8000 rpm, and keep the temperature for 10-15 minutes to obtain a cellulose solution;

[0014] A2, place the ferroferric oxide magnetic nanospheres and cellulose solution in a three-necked flask and mix them evenly, slowly add them dropwise to the coagulation bath, react for 24-26 hours, add propylene glycol triglycidyl ether, stir for 30-60 minutes, wash and dry to obtain magnetic cellulose microspheres;

[0015] The reaction principle for preparing cellulose ferroferric oxide magnetic nanospheres is as follows:

[0016] The sulfuric acid in the coagulation bath provides an acidic environment, and the sodium sulfate aggregates the cellulose molecules by changing the ionic strength, thereby enhancing the interaction between the cellulose and the ferroferric oxide magnetic nano-microspheres and forming a stable gel structure. The ions in the solution help to shield the electrostatic repulsion between the cellulose molecules, so that the magnetic nano-microspheres can be evenly distributed in the cellulose gel network to obtain magnetic cellulose microspheres. Glycerol triglycidyl ether is used as a cross-linking agent, and its epoxy group undergoes a ring-opening reaction with the hydrophilic group in the cellulose to form a stable ester bond or ether bond, which together with the coagulation bath promotes the formation of a three-dimensional network structure between the cellulose molecules, further promotes gelation, and improves the stability and dispersibility of the magnetic cellulose microspheres.

[0017] A3. Place the cellulose ferroferric oxide magnetic nanospheres, toluene solution and KH-792 in a three-necked flask at a temperature of 50-70°C, stir for 24-26 hours, and post-treat to obtain composite magnetic nanospheres.

[0018] The reaction principle for preparing composite magnetic nanospheres is:

[0019] The siloxy groups in KH-792 are hydrolyzed to generate hydroxysilane, which reacts with the hydroxyl groups on the surface of cellulose ferroferric oxide magnetic nanospheres to form siloxy bonds, introduce amino groups in KH-792, and provide reaction sites for subsequent amide reactions.

[0020] Furthermore, in step A1, the dosage ratio of urea, deionized water, NaOH and cellulose is 10-15g:200-400mL:7-10g:7-15g; in step A2, the coagulation bath is composed of sulfuric acid and sodium sulfate in a dosage ratio of 5-10mL:80-150g, and the dosage ratio of the ferroferric oxide magnetic nanospheres, cellulose solution and propylene glycol triglycidyl ether is 3-6g:15-30mL:10-15mL; in step A3, the dosage ratio of the cellulose ferroferric oxide magnetic nanospheres, toluene solution and KH-792 is 4-6g:100-120mL:1-2g, and the post-treatment includes: filtering the solution after the reaction, washing the solid with toluene and ethanol 1-2 times, and drying to obtain composite magnetic nanospheres.

[0021] Furthermore, in step A2, the method for preparing ferroferric oxide magnetic nanospheres comprises the following steps:

[0022] B1. Place FeCl3·6H2O, FeCl2·4H2O, deionized water, sodium citrate and PEG-4000 in a three-necked flask at a temperature of 50-70°C, stir for 15-30 minutes, add sodium hydroxide solution to adjust the pH to 11-11.2, and post-treat to obtain a crude product of ferroferric oxide magnetic nanoparticles;

[0023] B2. Place the crude product of ferroferric oxide magnetic nanoparticles and anhydrous sodium metasilicate in a three-necked flask at 80-100° C., keep the temperature for reaction for 30-40 minutes, and perform post-treatment to obtain ferroferric oxide magnetic nanoparticles.

[0024] The reaction principle for preparing ferroferric oxide magnetic nanospheres is:

[0025] Under alkaline conditions, ferroferric oxide magnetic nano-microspheres are prepared by a coprecipitation method, wherein sodium citrate is an anionic surfactant that can significantly reduce the surface tension of the solution and form a micelle structure in the solution, and the micelle can wrap the ferroferric oxide magnetic nano-microspheres, reduce the collision and interaction force between the magnetic nano-microspheres, prevent agglomeration, and provide a barrier at the same time; PEG-4000 is a nonionic surfactant, and as the length of the PEG-4000 molecular chain increases, an ordered template is formed on the surface of ferroferric oxide, which serves as a crystallization substrate and helps the ferroferric oxide nano-microspheres to be arranged more orderly, promotes the crystallization process of the nano-microspheres, and improves the crystallinity of the ferroferric oxide magnetic nano-microspheres; anhydrous sodium metasilicate has uniform magnetic nano-microspheres and a large specific surface area, can adjust the pH value, improve the surfactant performance, and produce a synergistic effect with the surfactant, and anhydrous sodium metasilicate can form a layer of SiO2 film on the surface of the magnetic nano-microspheres, inhibit the interaction between the magnetic nano-microspheres, and reduce agglomeration.

[0026] Furthermore, in step B1, the concentration of the sodium hydroxide solution is 1-2 mol / L, the dosage ratio of the FeCl2·4H2O, FeCl3·6H2O, deionized water, sodium citrate and PEG-4000 is 1.6-2.0 g: 3.8-4.5 g: 100-200 mL: 2-4 g: 2-4 g, and the post-treatment includes: filtering the reaction solution, washing the precipitate with deionized water for 1-2 times, drying, and grinding to obtain a crude product of ferroferric oxide magnetic nanospheres; in step B2, the dosage ratio of the crude product of ferroferric oxide magnetic nanospheres and anhydrous sodium metasilicate is 2-5 g: 5-10 g, and the post-treatment includes: separating the solid after the insulation reaction with a magnet, washing it with deionized water for 1-2 times, and drying to obtain ferroferric oxide magnetic nanospheres.

[0027] Furthermore, the present invention also provides a carboxylated ferroferric oxide magnetic nano-microsphere, wherein the carboxylated ferroferric oxide magnetic nano-microsphere is obtained by using a method for preparing carboxylated ferroferric oxide magnetic nano-microsphere.

[0028] The present invention has the following beneficial effects:

[0029] 1. In the process of preparing ferroferric oxide magnetic nano-microspheres, the present invention uses FeCl2·4H2O, FeCl3·6H2O, sodium citrate, PEG-4000 and anhydrous sodium metasilicate under alkaline conditions to prepare ferroferric oxide magnetic nano-microspheres by coprecipitation. In the reaction stage, sodium citrate can significantly reduce the surface tension of the solution, reduce the collision and interaction force between the magnetic nano-microspheres, prevent agglomeration, and provide a barrier to improve the dispersibility and acid resistance of ferroferric oxide magnetic nano-microspheres; PEG- The chain length of the 4000 molecular chain increases, forming an orderly template on the surface of the ferroferric oxide, which serves as a crystallization base, helps the ferroferric oxide nanospheres to arrange in a more orderly manner, promotes the crystallization process of the nanospheres, improves the crystallinity of the ferroferric oxide magnetic nanospheres, makes the spins of the iron ions more easily aligned, and enhances the saturated magnetic field strength of the ferroferric oxide magnetic nanospheres; anhydrous sodium metasilicate has uniform magnetic nanospheres and a large specific surface area, and can form a layer of SiO2 film on the surface of the magnetic nanospheres, thereby improving the stability of the ferroferric oxide magnetic nanospheres.

[0030] 2. In the process of preparing composite magnetic nanospheres, the present invention prepares magnetic cellulose microspheres by preparing cellulose into a dispersion and mixing it with ferroferric oxide magnetic nanospheres by a sol-gel method to form a stable three-dimensional network structure. The hydroxyl groups on the surface of cellulose are resistant to Cu in heavy metal wastewater. 2+ 、Al 3+ 、Zn 2+ and Ni 2+ A coordination complex can be formed to improve the stability, dispersibility and adsorption performance of the magnetic nano-microspheres in water. The nano-microspheres are then modified with a silane coupling agent KH-792 and amino groups are introduced to obtain composite magnetic nano-microspheres. The siloxy groups in KH-792 are hydrolyzed to generate hydroxysilanes, which react with the hydroxy groups on the surface of the cellulose ferroferric oxide magnetic nano-microspheres to form siloxy bonds and introduce amino groups to provide reaction sites for subsequent amide reactions. The siloxy bonds have extremely strong chemical stability and can withstand the erosion of acids, alkalis, solvents and other corrosive chemicals, and can improve the stability and acid resistance of the carboxylated ferroferric oxide magnetic nano-microspheres in water.

[0031] 3. In the process of preparing carboxylated ferroferric oxide magnetic nanospheres, the catalyst N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide are used to generate carboxylation to promote the formation of amide bonds between the amino groups on the surface of the composite magnetic nanospheres and part of the carboxyl groups of ethylenediaminetriaminepentaacetic acid, and multiple carboxyl groups of ethylenediaminetriaminepentaacetic acid are introduced into the ferroferric oxide magnetic nanospheres. The carboxyl groups interact with the hydroxyl groups in the cellulose to react with the Cu in the water. 2+ 、Al 3+ 、Zn 2+ and Ni 2+ The coordination reaction occurs to form a stable chelate, which improves the carboxylated ferroferric oxide magnetic nanospheres' ability to bind Cu in heavy metal wastewater. 2+ 、Al 3+ 、Zn 2+ and Ni 2+ Removal rate. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] This embodiment provides a method for preparing carboxylated ferroferric oxide magnetic nanospheres, comprising the following steps:

[0035] S1. Preparation of ferroferric oxide magnetic nanospheres

[0036] Weigh: FeCl3·6H2O1.6g, FeCl2·4H2O3.8g, deionized water 100mL, sodium citrate 2g and PEG-40002g in a three-necked flask, heat to 60°C, stir for 20min, add sodium hydroxide solution to adjust the pH to 11.1, filter the reaction solution, wash the precipitate with deionized water twice, dry, and grind to obtain crude ferroferric oxide magnetic nanospheres;

[0037] Weigh: 3 g of crude ferroferric oxide magnetic nanospheres and 5 g of anhydrous sodium metasilicate, place in a three-necked flask at 90° C., keep warm for 30 minutes, separate the solid after the reaction with a magnet, wash twice with deionized water, and dry to obtain ferroferric oxide magnetic nanospheres.

[0038] S2. Preparation of composite magnetic nanospheres

[0039] Weigh: 10 g of urea, 200 mL of deionized water, 7 g of NaOH and 7 g of cellulose, place them in a three-necked flask at 0°C, adjust the speed to 8000 rpm, and keep the temperature to react for 10 minutes to obtain a cellulose solution;

[0040] Weigh: 3 g of ferroferric oxide magnetic nanospheres and 15 mL of cellulose solution were placed in a three-necked flask and mixed evenly, then slowly added dropwise to the coagulation bath. After reacting for 24 h, 10 mL of propylene glycol triglycidyl ether was added, stirred for 30 min, and then washed and dried to obtain magnetic cellulose microspheres;

[0041] Weigh: 4 g of cellulose ferroferric oxide magnetic nanospheres, 100 mL of toluene solution and 1 g of KH-792, place in a three-necked flask at 60°C, stir for 24 h, filter the solution after the reaction, wash the solid twice with toluene and ethanol, and dry to obtain composite magnetic nanospheres.

[0042] S3. Preparation of carboxylated ferroferric oxide magnetic nanoparticles

[0043] Mix Na2H2PO4 and deionized water in a ratio of 3g:100mL to obtain a Na2H2PO4 solution for later use;

[0044] 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide are mixed uniformly in a weight ratio of 1:1 to obtain a catalyst for standby use;

[0045] Weigh: 2 g of ethylenediaminetriaminepentaacetic acid and 60 mL of ammonia water, place in a three-necked flask at 50°C, add acetic acid to adjust the pH to 6, add 1 g of catalyst, keep warm and react for 2 h to obtain a weak acid mixture;

[0046] Weigh: 2.5 g of composite magnetic nanospheres and 50 mL of weak acid mixture, place in a three-necked flask at 70°C, stir for 12 h, filter the reaction solution, wash the precipitate twice with Na2H2PO4 solution and deionized water, dry and grind to obtain carboxylated ferrosoferric oxide magnetic nanospheres.

[0047] Example 2

[0048] S1. Preparation of ferroferric oxide magnetic nanospheres

[0049] 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide are mixed uniformly in a weight ratio of 1:1 to obtain a catalyst for later use;

[0050] Weigh: FeCl3·6H2O1.8g, FeCl2·4H2O3.9g, deionized water 105mL, sodium citrate 2.1g and PEG-40002.1g into a three-necked flask, heat to 60°C, stir for 20min, add sodium hydroxide solution to adjust the pH to 11.0, filter the reaction solution, wash the precipitate with deionized water 1-2 times, dry, and grind to obtain a crude product of ferroferric oxide magnetic nanospheres;

[0051] Weigh: 2.1 g of crude ferroferric oxide magnetic nanospheres and 5.2 g of anhydrous sodium metasilicate, place in a three-necked flask at 90° C., keep warm for 30 minutes, separate the solid after the reaction with a magnet, wash twice with deionized water, and dry to obtain ferroferric oxide magnetic nanospheres.

[0052] S2. Preparation of composite magnetic nanospheres

[0053] Weigh: 10.5 g urea, 210 mL deionized water, 7.2 g NaOH and 7.2 g cellulose in a three-necked flask at 0°C, adjust the speed to 8000 rpm, and keep the temperature for 10 min to obtain a cellulose solution;

[0054] Weigh: 3.1 g of ferroferric oxide magnetic nanospheres and 18 mL of cellulose solution in a three-necked flask, mix well, slowly drop into the coagulation bath, react for 24 h, add 12 mL of propylene glycol triglycidyl ether, stir for 30 min, wash and dry to obtain magnetic cellulose microspheres;

[0055] Weigh: 4.2 g of cellulose ferroferric oxide magnetic nanospheres, 105 mL of toluene solution and 1.2 g of KH-792, place in a three-necked flask at 60°C, stir for 24 h, filter the solution after the reaction, wash the solid twice with toluene and ethanol, and dry to obtain composite magnetic nanospheres.

[0056] S3. Preparation of carboxylated ferroferric oxide magnetic nanoparticles

[0057] Mix Na2H2PO4 and deionized water in a ratio of 3g:100mL to obtain a Na2H2PO4 solution for later use;

[0058] 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide are mixed uniformly in a weight ratio of 1:1 to obtain a catalyst for later use;

[0059] Weigh: 2.2 g of ethylenediaminetriaminepentaacetic acid and 65 mL of ammonia water, place in a three-necked flask at 50°C, add acetic acid to adjust the pH to 6, add 1 g of catalyst, keep warm and react for 2 h to obtain a weak acid mixture;

[0060] Weigh: 2.7 g of composite magnetic nanospheres and 55 mL of weak acid mixture, place in a three-necked flask at 70°C, stir for 12 h, filter the reaction solution, wash the precipitate twice with Na2H2PO4 solution and deionized water, dry and grind to obtain carboxylated ferrosoferric oxide magnetic nanospheres.

[0061] Example 3

[0062] S1. Preparation of ferroferric oxide magnetic nanospheres

[0063] Weigh: FeCl3·6H2O2g, FeCl2·4H2O4g, deionized water 110mL, sodium citrate 2.4g and PEG-40002.3g into a three-necked flask, heat to 60°C, stir for 20min, add sodium hydroxide solution to adjust the pH to 11.2, filter the reaction solution, wash the precipitate with deionized water 1-2 times, dry, and grind to obtain a crude product of ferroferric oxide magnetic nanospheres;

[0064] Weigh: 2.5 g of crude ferroferric oxide magnetic nanospheres and 5.4 g of anhydrous sodium metasilicate, place in a three-necked flask at 90° C., keep warm for 30 minutes, separate the solid after the insulation reaction with a magnet, wash with deionized water 1-2 times, and dry to obtain ferroferric oxide magnetic nanospheres.

[0065] S2. Preparation of composite magnetic nanospheres

[0066] Weigh: 10.7 g urea, 210 mL deionized water, 7.5 g NaOH and 7.5 g cellulose in a three-necked flask at 0°C, adjust the speed to 8000 rpm, and keep the temperature for 10 min to obtain a cellulose solution;

[0067] Weigh: 3.4 g of ferroferric oxide magnetic nanospheres and 20 mL of cellulose solution in a three-necked flask, mix well, slowly drop into the coagulation bath, react for 24 h, add 14 mL of propylene glycol triglycidyl ether, stir for 30 min, wash and dry to obtain magnetic cellulose microspheres;

[0068] Weigh: 4.3 g of cellulose ferroferric oxide magnetic nanospheres, 108 mL of toluene solution and 1.4 g of KH-792, place in a three-necked flask at 60°C, stir for 24 hours, filter the solution after the reaction, wash the solid twice with toluene and ethanol, and dry to obtain composite magnetic nanospheres.

[0069] S3. Preparation of carboxylated ferroferric oxide magnetic nanoparticles

[0070] Mix Na2H2PO4 and deionized water in a ratio of 3g:100mL to obtain a Na2H2PO4 solution for later use;

[0071] 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide are mixed uniformly in a weight ratio of 1:1 to obtain a catalyst for later use;

[0072] Weigh: 2.5 g of ethylenediaminetriaminepentaacetic acid and 70 mL of ammonia water, place in a three-necked flask at 50°C, add acetic acid to adjust the pH to 6, add 0.5 g of catalyst, keep warm and react for 2 h to obtain a weak acid mixture;

[0073] Weigh: 2.9 g of composite magnetic nanospheres and 60 mL of weak acid mixture, place in a three-necked flask at 70°C, stir for 12 h, filter the reaction solution, wash the precipitate twice with Na2H2PO4 solution and deionized water, dry and grind to obtain carboxylated ferrosoferric oxide magnetic nanospheres.

[0074] Comparative Example 1

[0075] The difference between this comparative example and Example 3 is that sodium citrate, anhydrous sodium metasilicate and PEG-4000 are not added in step S1.

[0076] Comparative Example 2

[0077] The difference between this comparative example and Example 3 is that the step of preparing the cellulose dispersion in step S2 is eliminated, and in the process of preparing the composite magnetic nanospheres, ferroferric oxide magnetic nanospheres are used to replace the magnetic cellulose microspheres in an equal amount.

[0078] Comparative Example 3

[0079] The difference between this comparative example and Example 3 is that the catalyst is not added in step S3, and an equal amount of p-toluenesulfonic acid is used to replace the catalyst in the process of preparing carboxylated ferrosoferric oxide magnetic nanospheres.

[0080] Performance Test:

[0081] The saturation magnetic field strength of the carboxylated ferroferric oxide magnetic nanospheres prepared in Examples 1-3 and Comparative Examples 1-3 was tested with reference to the standard GB / T 21227-2021 "AC loss measurement - magnetometer measurement method for hysteresis loss of multi-filament composite superconducting materials";

[0082] Referring to the standard GB / T 43664.1-2024 "Determination of dispersibility of water treatment agents Part 1: Dispersed kaolin method", the dispersibility of the carboxylated ferroferric oxide magnetic nanospheres prepared in Examples 1-3 and Comparative Examples 1-3 was tested;

[0083] Referring to the standard GB / T 38431-2019 "Static multiple light scattering method for evaluating the stability of particle dispersion systems", the instability index of the carboxylated ferroferric oxide magnetic nanospheres prepared in Examples 1-3 and Comparative Examples 1-3 was tested;

[0084] Referring to the standard GB / T 5555-2003 "Test Method for Acid Resistance of Surfactants", the acid resistance level of the carboxylated ferroferric oxide magnetic nanospheres prepared in Examples 1-3 and Comparative Examples 1-3 was tested;

[0085] Referring to the standard GB / T 5555-2003 "Determination of heavy metal content in wastewater from catalyst production", the carboxylated ferroferric oxide magnetic nanoparticles prepared in Examples 1-3 and Comparative Examples 1-3 were tested for Cu 2+ 、Al 3+ 、Zn 2+ and Ni 2+ The removal rate was tested by preparing a solution containing Cu 2+ 、Al 3+ 、Zn 2+ and Ni 2+ The heavy metal mixed solution is used as heavy metal polluted wastewater, the carboxylated ferroferric oxide magnetic nanosphere sample and the heavy metal polluted wastewater are mixed at a dosage ratio of 1g:1L, and then according to the formula: Calculate the sample's effect on Cu in wastewater 2+ 、Al 3+ 、Zn 2+ and Ni 2+ The removal rate is as follows: C0 is the initial concentration of the prepared mixed heavy metal polluted wastewater, C1 is the concentration of the heavy metal polluted wastewater after the sample is adsorbed for 120 minutes. The specific data are shown in Table 1.

[0086] Table 1-Performance test data of each sample

[0087]

[0088] Data Analysis:

[0089] The data in the performance test data table of each sample in Table 1 are compared and analyzed. The saturation magnetic field strength of the carboxylated ferroferric oxide magnetic nano-microspheres prepared by the present invention is 90.3emu·g -1 , instability index is 0.102%, dispersibility is 87.2%, visual acid resistance is level 1 and removal rate is 98.5%, all data are better than the comparative example;

[0090] By comparing the data of Example 3 and Comparative Example 1, it can be found that the saturated magnetic field intensity and visual dispersion level of the magnetic nano-microspheres are significantly reduced, and the instability index and visual acid resistance level are increased, indicating that the addition of sodium citrate, anhydrous sodium metasilicate and PEG-4000 in the process of preparing ferroferric oxide magnetic nano-microspheres can reduce the collision and interaction force between the magnetic nano-microspheres, prevent agglomeration, and form a layer of SiO2 film on the surface of the magnetic nano-microspheres to prevent the ferroferric oxide magnetic nano-microspheres from contacting with acidic substances, oxygen and water vapor, prevent oxidative denaturation, and improve the stability and acid resistance of the ferroferric oxide magnetic nano-microspheres;

[0091] By comparing the data of Example 3 and Comparative Example 2, it can be found that the visual dispersion level of the magnetic nanoparticles and the Cu 2+ The adsorption amount was significantly reduced, and the acid resistance level and instability index were visually increased, indicating that the addition of cellulose and ferroferric oxide magnetic nanospheres formed a three-dimensional network structure, which improved the stability and dispersibility of the magnetic cellulose microspheres.

[0092] By comparing the data of Example 3 and Comparative Example 3, it can be found that the Cu 2+ The adsorption amount was significantly reduced and the instability index was increased, indicating that in the process of preparing carboxylated ferroferric oxide magnetic nanospheres, the use of catalysts further promoted the formation of amide bonds between the amino groups on the surface of the composite magnetic nanospheres and part of the carboxyl groups of ethylenediaminetriaminepentaacetic acid, introduced carboxyl groups, and N-hydroxysuccinimide could activate the carboxyl groups of ethylenediaminetriaminepentaacetic acid to form amide intermediates. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide could stabilize the intermediates, prevent hydrolysis, improve the efficiency of the amide reaction, ensure the stability of the cross-linking reaction, and improve the stability of the carboxylated ferroferric oxide magnetic nanospheres in water. Ethylenediaminetriaminepentaacetic acid contains multiple carboxyl groups. The introduced carboxyl groups act together with the hydroxyl groups in cellulose to react with Cu in water. 2+ 、Al 3+ 、Zn 2+ and Ni 2+ The coordination effect of carboxylated ferroferric oxide magnetic nanospheres increased the catalytic activity of Cu in heavy metal wastewater. 2+ 、Al 3+ 、Zn 2+ and Ni 2+ Removal rate.

[0093] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing carboxylated ferroferric oxide magnetic nanospheres, characterized in that: The following steps are involved: S1. Place ethylenediaminetriaminepentaacetic acid and ammonia water in a three-necked flask at a temperature of 30-60°C, add acetic acid to adjust the pH to 6-7, add a catalyst, and keep the temperature for reaction for 1-2 hours to obtain a weak acid mixture; S2. Place the composite magnetic nanoparticles and the weak acid mixture in a three-necked flask at a temperature of 60-80° C., stir for 12-15 hours, and perform post-treatment to obtain carboxylated ferroferric oxide magnetic nanoparticles.

2. The method for preparing carboxylated ferroferric oxide magnetic nanospheres according to claim 1, characterized in that: In step S1, the concentration of the ammonia water is 0.1-0.2 mol / L, the concentration of the acetic acid is 1.6-2.0 mol / L, the catalyst is composed of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide in a weight ratio of 1:1, and the dosage ratio of the ethylenediaminetriaminepentaacetic acid, the ammonia water and the catalyst is 2-5 g:60-80 mL:0.5-1 g; in step S2, the dosage ratio of the composite magnetic nanospheres and the weak acid mixed solution is 2.5-5 g:50-80 mL, and the post-treatment includes: filtering the reaction solution, washing the precipitate with 0.2 mol / L Na2H2PO4 solution and deionized water for 1-2 times, drying, and grinding to obtain carboxylated ferrosoferric oxide magnetic nanospheres.

3. The method for preparing carboxylated ferroferric oxide magnetic nanospheres according to claim 1, characterized in that: The preparation method of the composite magnetic nanospheres comprises the following steps: A1. Place urea, deionized water, NaOH and cellulose in a three-necked flask at a temperature of -15-15°C, adjust the speed to 8000 rpm, and keep the temperature for 10-15 minutes to obtain a cellulose solution; A2, place the ferroferric oxide magnetic nanospheres and cellulose solution in a three-necked flask and mix them evenly, slowly add them dropwise to the coagulation bath, react for 24-26 hours, add propylene glycol triglycidyl ether, stir for 30-60 minutes, wash and dry to obtain magnetic cellulose microspheres; A3. Place the cellulose ferroferric oxide magnetic nanospheres, toluene solution and KH-792 in a three-necked flask at a temperature of 50-70°C, stir for 24-26 hours, and post-treat to obtain composite magnetic nanospheres.

4. The method for preparing carboxylated ferroferric oxide magnetic nanospheres according to claim 3, characterized in that: In step A1, the dosage ratio of urea, deionized water, NaOH and cellulose is 10-15g:200-400mL:7-10g:7-15g; in step A2, the coagulation bath is composed of sulfuric acid and sodium sulfate in a dosage ratio of 5-10mL:80-150g, and the dosage ratio of the ferroferric oxide magnetic nanospheres, the cellulose solution and propylene glycol triglycidyl ether is 3-6g:15-30mL:10-15mL; in step A3, the dosage ratio of the cellulose ferroferric oxide magnetic nanospheres, the toluene solution and KH-792 is 4-6g:100-120mL:1-2g, and the post-treatment includes: filtering the solution after the reaction, washing the solid with toluene and ethanol for 1-2 times, and drying to obtain the composite magnetic nanospheres.

5. The method for preparing carboxylated ferroferric oxide magnetic nanospheres according to claim 3, characterized in that: In step A2, the method for preparing ferroferric oxide magnetic nanospheres comprises the following steps: B1. Place FeCl3·6H2O, FeCl2·4H2O, deionized water, sodium citrate and PEG-4000 in a three-necked flask at a temperature of 50-70°C, stir for 15-30 minutes, add sodium hydroxide solution to adjust the pH to 11-11.2, and post-treat to obtain a crude product of ferroferric oxide magnetic nanoparticles; B2. Place the crude product of ferroferric oxide magnetic nanoparticles and anhydrous sodium metasilicate in a three-necked flask at 80-100° C., keep the temperature for reaction for 30-40 minutes, and perform post-treatment to obtain ferroferric oxide magnetic nanoparticles.

6. The method for preparing carboxylated ferroferric oxide magnetic nanospheres according to claim 5, characterized in that: In step B1, the concentration of the sodium hydroxide solution is 1-2 mol / L, the dosage ratio of the FeCl2·4H2O, FeCl3·6H2O, deionized water, sodium citrate and PEG-4000 is 1.6-2.0 g: 3.8-4.5 g: 100-200 mL: 2-4 g: 2-4 g, and the post-treatment comprises: filtering the reaction solution, washing the precipitate with deionized water for 1-2 times, drying, and grinding to obtain a crude product of ferroferric oxide magnetic nano-microspheres; in step B2, the dosage ratio of the crude product of ferroferric oxide magnetic nano-microspheres and anhydrous sodium metasilicate is 2-5 g: 5-10 g, and the post-treatment comprises: separating the solid after the insulation reaction with a magnet, washing it with deionized water for 1-2 times, and drying to obtain ferroferric oxide magnetic nano-microspheres.

7. A carboxylated ferroferric oxide magnetic nanosphere, characterized in that: The carboxylated ferroferric oxide magnetic nano-microspheres are obtained by using the preparation method of carboxylated ferroferric oxide magnetic nano-microspheres according to any one of claims 1 to 6.